Micronutrient Status Assessment in Saudi Patients Prior to Laparoscopic Sleeve Gastrectomy: A Retrospective Study. - SALEEM, Rimah; M. RAMADAN, Majed; S. SHEIK, Muhammad; S. BAHAMAN, Juhaina; ZARROL, Samah; GARAWEEN, Ghada; ALHUSSEINI, Noara K (Nutrición Clínica y Dietética Hospitalaria, 2023)
Objective: This study aimed to investigate demographic trends and characteristics of Saudi patients undergoing LSG in different regions of the country. Methods: We retrospectively collected preoperative data from 285 patients who underwent LSG between 2016 and 2021 at a tertiary care centre. Patients’ demographic data including the body mass index (BMI) and blood profiles before LSG, were analysed. Results: The mean patient age was 46 years, and the mean preoperative BMI was 36.50 kg/m2. Females comprised more than two-thirds of the patients (69%). Among the pre-operative blood parameters, haemoglobin and vitamin B1 deficiency were noticeable in both sexes. Conclusion: This predictive analysis could assist surgeons in identifying common deficiencies and expected post-surgical micronutrient deficiencies relevant to undesirable complications.